Data-driven thermal fault detection of lithium-ion batteries - Yee, Eugene Jun Jian (Nanyang Technological University, 2022)
The electric vehicle (EV) industry is beginning to prosper at an unprecedented rate due to laws against the production of internal combustion engine (ICE) vehicles. The laws were implemented as the supply of petrol is running out and due to global warming concerns. Most if not all electric vehicles rely on lithium-ion batteries (LIBs) and rapid technological advancement of LIBs in their power density and energy poses reliability and safety concerns. One of the critical hazards is thermal fault as it can be potentially catastrophic and may cause fire accidents or even explosions.